2001
DOI: 10.1056/nejm200104263441702
|View full text |Cite|
|
Sign up to set email alerts
|

DNA Content as a Prognostic Marker in Patients with Oral Leukoplakia

Abstract: The DNA content in cells of oral leukoplakia can be used to predict the risk of oral carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
148
1
6

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(158 citation statements)
references
References 50 publications
3
148
1
6
Order By: Relevance
“…Our prognostic study 26 did not indicate whether standard treatment in the form of preventive excision of leukoplakia would be adequate treatment. Conceivably, local treatment in the form of surgical excision could prevent later carcinomas.…”
Section: Surgical Resection Of Leukoplakiamentioning
confidence: 68%
See 2 more Smart Citations
“…Our prognostic study 26 did not indicate whether standard treatment in the form of preventive excision of leukoplakia would be adequate treatment. Conceivably, local treatment in the form of surgical excision could prevent later carcinomas.…”
Section: Surgical Resection Of Leukoplakiamentioning
confidence: 68%
“…Therefore, reliable predictive markers that may be used for making treatment decisions at an early stage of disease development are greatly needed. A number of such markers have evolved during the past decade, [23][24][25][26] and some of them are finding their way into the clinical work-up of patients with oral putatively premalignant lesions. 26 …”
Section: Traditional Prognostic Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al (2002) demonstrated that chewing tobacco (areca quid) resulted in the formation of ROS in the oral cavity causing oxidative DNA damage to the surrounding tissues. Further support can be found in a report demonstrating that premalignant mucosal lesions and low-grade carcinomas express DNA aberrations following a pathway of exposure to free radicals (Sudb et al, 2001). Moreover, Bloching et al (2001) recently found increased genotoxic activity in the saliva of smokers with a highly significant additional increase of genotoxicity measured in smoking and drinking individuals.…”
mentioning
confidence: 67%
“…При этом наличие тетраплоидных клеток не явля-ется фактором неизбежного прогрессирования заболевания. Опухоли, содержащие тетраплоидные клетки, с равной вероят-ностью могли и регрессировать [14,15]. Были также представле-ны доказательства, что полиплоидизация является распростра-ненной причиной опухолевой эволюции генома у человека и коррелирует с прогрессированием заболевания [16,17].…”
unclassified